Collection of autologous monocytes for dendritic cell vaccination therapy in metastatic melanoma patients - Nguyen, Xuan-Duc; Eichler, Hermann; Sucker, Antje; Schadendorf, Dirk; Klüter, Harald (Transfusion, 2002)
BACKGROUND: Dendritic cells (DCs) for immunotherapy of malignant melanoma can be generated from partially enriched monocytes prepared from PBMNCs. The feasibility of a single steady-state leukapheresis procedure to enrich monocytes for a complete vaccination series with up to 10 vaccinations was investigated. STUDY DESIGN AND METHODS: Thirty-eight patients (27 males and 11 females) with metastatic melanoma were enrolled in the study. All leukapheresis procedures were performed by a continuous flow method (Spectra, Cobe BCT) with a standard MNC program. RESULTS: An average of 11.7 L (range, 8-14 L) of whole blood was processed within 197.3 ± 23.7 minutes, and a mean of 13.5 ± 5.7 × 109 WBCs in a final volume of 191.0 ± 24.2 mL was collected. The MNC purity in the apheresis component was 81.5 ± 15.1 percent, from which 29.8 ± 14.7 percent were monocytes. Thus, 11.0 ± 5.0 × 109 MNCs and 3.2 ± 2.0 × 109 monocytes were collected per procedure. Linear regression analysis revealed a high correlation between the absolute number of monocytes in peripheral blood before the apheresis procedure and the number of monocytes in the collected component (r = 0.74, p < 0.0001). For the generation of DCs, 1.6 ± 0.8 × 109 MNCs were plated into culture dishes; 3.2 ± 1.8 percent of the cultured cells matured to DCs, which resulted in 56.5 ± 49.4 × 106 DCs (range, 6.3-178) per patient for the complete vaccination series. CONCLUSION: A target dose of monocytes for the complete vaccination series could be obtained by a single convenient, safe, steady-state leukapheresis procedure in each patient without the need for G-CSF mobilization. The absolute number of monocytes in peripheral blood before the apheresis procedure is the best predictive variable for the yield of monocytes in the apheresis component.
Gesehen am 11.11.2020